Parent-reported phenotype data on chromosome 6 aberrations collected via an online questionnaire: data consistency and data availability - Aafke Engwerda; Barbara Frentz; Eleana Rraku; Nadia F. Simoes de Souza; Morris A. Swertz; Mirjam Plantinga; Wilhelmina S. Kerstjens-Frederikse; Adelita V. Ranchor; Conny M. A. van Ravenswaaij-Arts (Orphanet Journal of Rare Diseases, 2023)
Abstract Background Even with the introduction of new genetic techniques that enable accurate genomic characterization, knowledge about the phenotypic spectrum of rare chromosomal disorders is still limited, both in literature and existing databases. Yet this clinical information is of utmost importance for health professionals and the parents of children with rare diseases. Since existing databases are often hampered by the limited time and willingness of health professionals to input new data, we collected phenotype data directly from parents of children with a chromosome 6 disorder. These parents were reached via social media, and the information was collected via the online Chromosome 6 Questionnaire, which includes 115 main questions on congenital abnormalities, medical problems, behaviour, growth and development. Methods Here, we assess data consistency by comparing parent-reported phenotypes to phenotypes based on copies of medical files for the same individual (n = 20) and data availability by comparing the data available on specific characteristics reported by parents (n = 34) to data available in existing literature (n = 39). Results The reported answers to the main questions on phenotype characteristics were 85–95% consistent, and the consistency of answers to subsequent more detailed questions was 77–96%. For all but two main questions, significantly more data was collected from parents via the Chromosome 6 Questionnaire than was currently available in literature. For the topics developmental delay and brain abnormalities, no significant difference in the amount of available data was found. The only feature for which significantly more data was available in literature was a sub-question on the type of brain abnormality present. Conclusion This is the first study to compare phenotype data collected directly from parents to data extracted from medical files on the same individuals. We found that the data was highly consistent, and phenotype data collected via the online Chromosome 6 Questionnaire resulted in more available information on most clinical characteristics when compared to phenotypes reported in literature reports thus far. We encourage active patient participation in rare disease research and have shown that parent-reported phenotypes are reliable and contribute to our knowledge of the phenotypic spectrum of rare chromosomal disorders.